God as Guardian and Enemy of the Human Soul/Life. The Cultural and Theological Code of the nepeš in 1 Sam 25:29 - Dziadosz, Dariusz Antoni; Wojnicki, Arkadiusz (Verbum Vitae, 2022)
The cycles of traditions about Saul’s rise to power and reign (1 Sam 7:2–12:25; 13:1–15:31) and David’s ascension to the throne (1 Sam 16:1 – 2 Sam 5:5) portray human life as constantly under threat while simultaneously remaining in all circumstances in the hands of YHWH and dependent on His will. In order to understand the Deuteronomist’s perspective on the life/soul of a human being, one has to explore the meaning of the Hebrew term nepeš in the source material he edited. This publication, using the historical-critical method, analyses the meaning of the concept of nepeš in 1 Sam 25:29 to show on this basis: (1) literary, editorial and historical-cultural background of this verse in the context of the whole cycle of tradition: 1 Sam 16:1 – 2 Sam 5:5; (2) exegetical analysis of nepeš and other key terms used in 1 Sam 25:29; (3) theological ideas present in the Hebrew text and their implications for the biblical concept of the human soul. This is because Abigail’s blessing shows the image of God characteristic of historical books of the Old Testament, as well as sheds light on the character of David and his role in the inauguration of monarchical power in Israel. Furthermore, it allows new aspects of the semantic field of the term nepeš to be discovered.